(untitled) (Hackensack, N.J., 2004)
This volume is a compilation of 50 articles representing the scientific and technical advances in various aspects of system dynamics, instrumentation, measurement techniques, and control. It serves as an important resource in the field. The topics include state-of-the-art contributions in the fields of dynamics and control of nonlinear, hybrid, stochastic, time-delayed and piecewise affine systems; nonlinear control theory; control of chaotic systems; adaptive, model predictive and real-time controls, with applications involving vehicular systems, fault diagnostics, and flexible and cellular manufacturing systems, vibration suppression, biomedical, mobile robots, etc.
Keywords: Engineering,Dynamics,System analysis; Mathematical models; Congresses